Особливості побудови управлінського обліку витрат підприємства за центрами відповідальності - Чуприна, Людмила Вікторівна; Зарічна, Ніна Сергіївна (НТУ "ХПІ", 2017)
Ефективне управління витратами підприємства прямо залежить від ефективності обліку, контролю та аналізу використаних ресурсів.Організація обліку витрат за "місцями виникнення" та "центрами відповідальності" є одним із основних підходів до побудови ефективної системи – управлінського обліку витрат. У статті розглянуто економічну природу "місць виникнення" витрат, "центрів відповідальності", особливості організації та обліку витрат за "місцями виникнення" та "центрами відповідальності".

The effective management of enterprise expenses straight depends on efficiency of account, control and analysis of the used resources. Organization of account of expenses after the "places of origin" and "centres of responsibility" is one of the basic going near the construction of the effective system – administrative account of expenses. In the article economic nature of "places of origin" of expenses, "centres of responsibility", feature of organization and account of expenses, is considered after the "places of origin" and "centres of responsibility". The necessity of costs centers and responsibility centers singling out and their influence on costs accounting organization at an enterprise are proven.
Features of building of the administrative account of expenses of the enterprise on the responsibility centers
Keywords: центр витрат; калькулювання; собівартість; бухгалтерська система; метод порівняння; метод бюджетування; costs; costs centre; responsibility centre; accounting organization; calculation; prime cost